Quantification of Groundwater Nitrate Loading after Raspberry Field Renovation Using High‐Resolution Passive Diffusion Sampling. Issue 6 (1st November 2019) - Loo, Shawn E.; Zebarth, Bernie J.; Ryan, M. Cathryn; Malekani, Farzin; Cey, Edwin E.; Suchy, Martin; Forge, Tom A.
Abstract : The Abbotsford‐Sumas Aquifer is a permeable, unconfined aquifer in British Columbia, Canada, where raspberry ( Rubus idaeus L.) production is an important source of groundwater NO3 contamination. Renovation of raspberry fields (i.e., canes chopped, soil tilled and fumigated, and spring manure application prior to replanting), which typically occurs every 6 to 10 yr in response to decreased crop vigor, has been suggested as a possible cause of significant interannual variation in groundwater NO3 concentrations. This study used high‐resolution passive diffusion sampling to quantify the magnitude and timing of NO3 loading to shallow groundwater from a commercial raspberry field during a 6‐yr (2009–2015) monitoring period after crop renovation. After renovation, the annual NO3 loading increased from ∼95 kg N ha −1 in Year 1 to ∼245 kg N ha −1 in Year 2 and decreased to ∼85 kg N ha −1 in Year 3. The average annual NO3 loading from Years 4 to 6 (72 kg N ha −1 ) was assumed to reflect annual loading without a renovation effect, and the increased loading during Years 1 to 3 was attributed to renovation. Renovation contributed an estimated 33 to 23% of total groundwater NO3 from this field for a 6‐ to 10‐yr renovation cycle. Most of the NO3 loading associated with renovation occurred in Year 2 and was attributed to the manure application. The increased NO3 loading after renovation likely contributes to the spatial and temporally varying NO3 patterns observed in the aquifer. Reducing manure applications during renovation and decreasing renovation frequency have the potential to decrease the groundwater NO3 concentration. Core Ideas: We estimated NO3 flux using vertically high‐resolution groundwater sampling and Darcy flux. Loading was estimated under raspberry field for 6 yr after stand renovation. Renovation frequency is an important control on long‐term NO3 concentration. An estimated one‐third to one‐quarter of groundwater NO3 was from renovation in a 6‐ to 10‐yr cycle. Manure was potentially the primary source of additional NO3 loading during renovation.